2007
DOI: 10.1111/j.1365-2745.2007.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Flora of the British Isles: Juniperus communis L.

Abstract: Summary1. This account reviews information on all aspects of the biology of Juniperus communis that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles : distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history and conservation. 2. Juniperus communis (jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(188 citation statements)
references
References 209 publications
(506 reference statements)
3
181
1
3
Order By: Relevance
“…The reason for this is that Juniperus ignites easily, and its high content of volatile oils makes it highly susceptible to burning. In most cases fire extirpates shrubs locally (ANPD, BNPD, KNPD; Ónodi et al, 2008, Thomas et al, 2007). Fire is also an important natural determinant of the dynamic of ecosystems dominated by J. communis.…”
Section: Woody Speciesmentioning
confidence: 99%
“…The reason for this is that Juniperus ignites easily, and its high content of volatile oils makes it highly susceptible to burning. In most cases fire extirpates shrubs locally (ANPD, BNPD, KNPD; Ónodi et al, 2008, Thomas et al, 2007). Fire is also an important natural determinant of the dynamic of ecosystems dominated by J. communis.…”
Section: Woody Speciesmentioning
confidence: 99%
“…Today, juniper population is found in a wide range of open habitats, at varying altitudes and growing in a wide range of soil types (Cooper et al) It favors free-draining soils, rocky outcrops and rarely inhabits wet conditions (Thomas et al, 2007). The species has a low tolerance to shade (Grubb et al, 1996) and is gradually excluded from woodland.…”
Section: Resultsmentioning
confidence: 99%
“…Junipers produce a large proportion of apparentlyviablebutemptyseeds (Thomas& al., 2007), but proportions of viable seeds obtained in this study are lower than those found for J. communis in Iberian Peninsula (García & al., 2000) or for the endangered J. oxycedrus ssp.macrocarpa (Juan&al.,2003(Juan&al., , 2006andverylowwhencomparedtosimilar studies with other junipers (Rumeu & al., 2009) (García & al., 2000;Wesche&al.,2005;Otto&al.,2012).…”
Section: Discussionmentioning
confidence: 99%
“…Along with irregular seed production, most junipers have germination limitations duetoageofthejuniperbush,insectpredation and empty seeds (Thomas & al., 2007;Verheyen&al.,2009),andalsotodormancy directlyassociatedwiththeembryo,theseed coat impermeability or the presence of germinationinhibitors (Juan&al.,2006).These recruitmentlimitationsmightalsobeexacerbatedbyclimatealterations,sincemorefrequentwarmeranddriersummerscaninfluence seed production and viability due to water deficit stress (García & al., 1999;García & al., 2000;Muñoz-Reinoso, 2003). According to IUCN Red List of Species, from the 1052 gymnosperm known species, 399areconsideredthreatened(38%),anumber that more than doubled in the last 17 years (IUCN, 2014).…”
Section: Introductionmentioning
confidence: 99%